40Ar/39Ar ages of lunar impact glasses: Relationships among Ar diffusivity, chemical composition, shape, and size. (15th July 2015) - Zellner, N.E.B.; Delano, J.W.
Abstract: Lunar impact glasses, which are quenched melts produced during cratering events on the Moon, have the potential to provide not only compositional information about both the local and regional geology of the Moon but also information about the impact flux over time. We present in this paper the results of 73 new 40 Ar/ 39 Ar analyses of well-characterized, inclusion-free lunar impact glasses and demonstrate that size, shape, chemical composition, fraction of radiogenic 40 Ar retained, and cosmic ray exposure (CRE) ages are important for 40 Ar/ 39 Ar investigations of these samples. Specifically, analyses of lunar impact glasses from the Apollo 14, 16, and 17 landing sites indicate that retention of radiogenic 40 Ar is a strong function of post-formation thermal history in the lunar regolith, size, and chemical composition. This is because the Ar diffusion coefficient (at a constant temperature) is estimated to decrease by ∼3–4 orders of magnitude with an increasing fraction of non-bridging oxygens, X(NBO), over the compositional range of most lunar impact glasses with compositions from feldspathic to basaltic. Based on these relationships, lunar impact glasses with compositions and sizes sufficient to have retained ∼90% of their radiogenic Ar during 750 Ma of cosmic ray exposure at time-integrated temperatures of up to 290 K have been identified and are likely to have yielded reliable 40 Ar/ 39 Ar ages of formation. Additionally, ∼50% of the identified impact glass spheres have formation ages of ⩽500 Ma, while ∼75% of the identified lunar impact glass shards and spheres have ages of formation ⩽2000 Ma. Higher thermal stresses in lunar impact glasses quenched from hyperliquidus temperatures are considered the likely cause of poor survival of impact glass spheres, as well as the decreasing frequency of lunar impact glasses in general with increasing age. The observed age-frequency distribution of lunar impact glasses may reflect two processes: (i) diminished preservation due to spontaneous shattering with age; and (ii) preservation of a remnant population of impact glasses from the tail end of the terminal lunar bombardment having 40 Ar/ 39 Ar ages up to 3800 Ma. A protocol is described for selecting and analyzing lunar impact glasses.